Whole Exome Sequencing Identifies Three Novel Mutations in the ASPM Gene From Saudi Families Leading to Primary Microcephaly - Naseer, Muhammad Imran; Abdulkareem, Angham Abdulrahman; Muthaffar, Osama Yousef; Sogaty, Sameera; Alkhatabi, Hiba; Almaghrabi, Sarah; Chaudhary, Adeel G. (Frontiers in Pediatrics, 2021)
Autosomal recessive Primary Microcephaly (MCPH) a neurodevelopmental defect that is characterized by reduced head circumference at birth along with non-progressive mental retardation. Till date, 25 genes related to MCPH have been reported so far in humans. ASPM (abnormal spindle-like, microcephaly associated) gene is among the most frequently mutated MCPH gene. We studied seven different families having primary microcephaly from different regions of Saudi Arabia. Whole exome sequencing (WES) and Sanger sequencing was done to identify the genetic defect. Collectively, three novel variants were identified in ASPM gene from three different primary microcephaly families. Family 1, showed a homozygous frameshift mutation c.1003del. (p.Val335*) in exon 3 of ASPM gene and family 2 showed homozygous deletion variant c.1047del G, p.Gln349HisfsTer18 while in family 3 we identified a missense mutation c.5623A>G leading to change in protein p.Lys1875Glu in the exon 18 of ASPM gene to underlie the disorder. The identified respective mutations were ruled out in 100 healthy control samples. In conclusion we found three novel mutations in ASPM gene in Saudi families that will help to establish a disease database for specified mutations in Saudi population and will further help to identify the strategies to tackle primary microcephaly from Kingdom.